Model Pengujian Lingkungan Kerja Fisik, Pelatihan Kerja serta Kepuasan terhadap Kinerja Karyawan PT. Andalas Agro Lestari Logas - Silvia Sari Sitompul (COSTING : Journal of Economic, Business and Accounting, 2018)
The aim of this research is to find out the effect of physhical workplace, training, satisfaction of work in partial and simultaneously also to find out which variable that give the most effect to employees peformance at PT. Andalas Agrolestari. Total of samples that will be use in this research are 71 employees that working on field. The analysis of Data that we will use in this research is the regression of double linear. Base on the result of partial test it is known that pyhsical workplace and satisfiaction of work affecting employees peformance meanwhile, training not affecting employees peformance at PT. Andalas Agrolestari. Between the three independent variable satisfication of work have a dominant influential the most. Meanwhile, three of the independent variable simultaneously affecting employees peformance together at PT. Andalas Agrolestari therefore, this hypothesis get accepted. Base on the research result it is known physical workplace and satisfaction of work give an influent towards employees peformance at PT. Andalas Agrolestari.Therefore it will be more wisely for the company to be able to control the problem from physical workplace and satisfaction of work from the employees so their peformance will stay high. Keywords: Physhical Workplace, Training, Satisfaction of Work and Employee Peformance